2002
DOI: 10.1515/bc.2002.165
|View full text |Cite
|
Sign up to set email alerts
|

Foldase Function of the Cathepsin S Proregion Is Strictly Based upon Its Domain Structure

Abstract: Folding of cathepsin S, like other cathepsin L-like proteases, depends on its proregion. The major part of the proregion forms a small domain distal from the catalytic centre, suggesting function(s) beyond active-site shielding. Using an optimised in vitro trans-refolding assay, we compared reactivation of denatured cathepsin S by the genuine propeptide, wild-type and ten selected mutants. Including structural data and binding constants, we identified the prodomain core and the hairpin region to be important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Because the pro‐tyrosinase form contains no predicted transmembrane helices and is indeed fully soluble in E. coli (see above), we suggest that the C‐terminal extension in this case has a purely inhibitory function and neither a significant role in stabilizing the enzyme, nor a chaperone‐like function during folding, as has been proposed for other N‐terminal/C‐terminal zymogen‐like systems [40]. It remains to be determined whether this is also the case for other pro‐tyrosinase forms.…”
Section: Resultsmentioning
confidence: 67%
“…Because the pro‐tyrosinase form contains no predicted transmembrane helices and is indeed fully soluble in E. coli (see above), we suggest that the C‐terminal extension in this case has a purely inhibitory function and neither a significant role in stabilizing the enzyme, nor a chaperone‐like function during folding, as has been proposed for other N‐terminal/C‐terminal zymogen‐like systems [40]. It remains to be determined whether this is also the case for other pro‐tyrosinase forms.…”
Section: Resultsmentioning
confidence: 67%
“…They seem to retain their secondary structure over a wide pH range from 6.5 to 3.0 (Jerala et al, 1998). Several experiments have shown that addition of recombinant propeptides can efficiently catalyze the refolding of denatured mature cysteine proteinases (Pietschmann et al, 2002;Yamamoto et al, 2002;Capetta et al, 2002). With respect to cathepsin S, this effect was strongly dependent on the three-dimensional structure of the propeptide.…”
Section: Folding Assistancementioning
confidence: 99%
“…With respect to cathepsin S, this effect was strongly dependent on the three-dimensional structure of the propeptide. Mutants affecting the aromatic Trp core of the propeptide showed a much weaker foldase effect than the wild type propeptide (Pietschmann et al, 2002). A mutation in the conserved GNFD motif (N70pI/F72pI) of the F. hepatica cathepsin L propeptide also diminished the foldase function of the propeptide (Capetta et al, 2002).…”
Section: Folding Assistancementioning
confidence: 99%
See 1 more Smart Citation
“…We are at present investigating the propeptide of cathepsin S, a member of the cathepsin L-like papain subfamily (Karrer et al, 1993;Kirschke et al, 1986Kirschke et al, , 1989Wiederanders et al, 1992). The 99-residue cathepsin S propeptide (MW 12 kDa) can be regarded as a foldase which promotes the folding process of the mature enzyme (Kreusch et al, 2000;Schilling et al, 2001;Pietschmann et al, 2002). This function requires the tertiary structure of the isolated propeptide, which folds independently of the other parts of the molecule (Maubach et al, 1997;Schilling et al, 2001).…”
Section: Introductionmentioning
confidence: 99%